Fast setting tricalcium silicate/magnesium phosphate premixed cement for root canal filling. Issue 3 (15th February 2018) - Zhou, Yanling; Xu, Chen; Wang, Xiaoya; Dou, Yuandong; Huan, Zhiguang; Chang, Jiang
Abstract: MTA-based root-end filling is a promising therapeutic approach for root repair, however, difficult handling characteristics, presence of toxic elements in the material composition and long setting time are main drawbacks for clinical applications. The purpose of this study was to develop a novel fast setting silicate based premixed cement for endodontic use. The premixed cement contained tricalcium silicate (C3S) as the main constituent for hydration, magnesium phosphate cement (MPC) as setting accelerators and glycerol as water-miscible liquid. The physicochemical properties and antibacterial property of the novel cements were evaluated. Moreover, biocompatible zirconium oxide (ZrO2 ) was chosen as radiopacifying agent added into the premixed cement. The radiopacity, physicochemical properties, antibacterial property and cytotoxicity of the radiopaque premixed calcium silicate based cements were evaluated. The setting time of the premixed MPC/C3S cements could be modulated within the range from 70 min to 205 min by adjusting the content of MPC. Meanwhile, the premixed MPC/C3S cement displayed good flowability and injectability when the amount of MPC less than 20%. The addition of ZrO2 provided the premixed MPC/C3S cement with excellent radiopacity while had no significant effects on the setting time, flowability, film thickness, injectability and washout resistance. Moreover, the premixed cement with or without ZrO2 had good antibacterial property and cytotoxicity. Our results indicated that the premixed MPC/C3S/ZrO2 cement could be considered as a promising candidate for application in endodontics owing to its desirable physicochemical properties, antibacterial activity and cytocompatibility, especially relatively short setting time and good sealing ability.